Influence of Chromium Propionate Supplementation on Feed Intake, Growth Rate, Haematological and Antioxidant Enzymes Profile in Sahiwal Calves During Summer Season - Kumar, Suresh; Singh, S. V.; Singh, A. K.; Maibam, Uttarani; ., Beenam; Upadhyay, R. C. (Indian Journal of Animal Nutrition, 2018)
Twelve Sahiwal calves were divided into 2 group of 6 animals each All the animals in both the groups were fed as per NRC requirements, however, the animals in control group were given no chromium while in treatment 1 group, the animals were supplemented with 0.5 ppm chromium in form of chromium propionate in order to study feed intake and blood parameters during summer season. Body weight gain, DM intake and haematological parameters were found to be similar in both the groups. The activities of superoxide dismutase, glutathione reductase and glutathione peroxidase were also similar in both the groups, however, catalase activity was lower (P